Primary Histiocytic Sarcoma, an Extremely Rare Neoplasm: Report of a Case Presenting as a Skin Lesion - Shateri Amiri, Bahareh; Esfandbod, Mohsen; Ghanadan, Alireza; Taslimi, Reza; Kosari, Farid (Reports of Radiotherapy and Oncology, 2020)
Histiocytic sarcoma (HS) is a very rare neoplasm of hematopoietic origin characterized by the proliferation of malignant cells that have the morphological and immunohistochemical features of mature tissue histiocytes, with only a few cases reported. Most patients with symptoms of the unilateral or multichannel disease are more involved with the intestines, skin, and soft tissues, palpable mass lesions, and compressions of adjacent organs, such as intestinal obstruction, or constitutional symptoms (e.g., fever and weight loss). In this study, we reported a 56-year-old man with a six-month history of a cutaneous plaque lesion on the left arm’s posterior surface. He underwent skin lesion biopsy, histopathologic examination, and immunohistochemistry that was compatible with histiocytic sarcoma. Since surgical resection not deemed appropriate, our patient underwent aggressive multiagent chemotherapy with six cycles of ICE (ifosfamide, mesna, carboplatin, and etoposide) regimen and radiotherapy. After the completion of chemoradiotherapy, the skin lesion was completely disappeared. The patient is currently coming to us for the follow-up without any recurrence of the disease.